Coaching disadvantaged young people : evidence from firm level data - Mohrenweiser, Jens [Verfasser]; Pfeiffer, Friedhelm [Verfasser] (My University, 2015)
"In Germany, apprenticeship training firms currently face a shrinking number of qualified school-leavers because of smaller birth cohorts and an increasing proportion of school leavers aiming for higher education. This paper investigates whether a programme that supports firms to train disadvantaged youth can reduce recruiting difficulties in apprentice training firms. Based on unique firm-level data from the metal and electronic industry in Baden-Württemberg from 2010 to 2013, we apply instrumental variable and difference-in-difference estimations and find no significant short-term causal impact of the programme." (Authors' abstract, BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; P 1.7 Benachteiligte; S 2.3.2 Programme in der Berufsbildung; Betriebliche Berufsausbildung; Metallindustrie; Elektroindustrie; Benachteiligter Jugendlicher; Coaching; Sozialpädagogische Betreuung; Ausbildungsbegleitende Hilfe; Evaluation; Baden-Württemberg